Empowerment of the elderly posyandu during the Covid-19 pandemic - Sukamta Sukamta; Indardi Indardi; Sholeh Harun; Akmal Iraqi; Tito Ardhiyanto Perdana; Mufida Sagitania Husna Ayustri; Annisa Maulin; Istika Amrina Rosyada; Muhammad Fatah Nafi (Universitas Muhammadiyah Magelang, 2022)
Elderly Posyandu provide not only health services to the elderly, but also social, religious, educational, skills, sports, arts, and cultural services, among other things. The difficulties encountered include how to provide advice and implement health protocols during the implementation of the Elderly Posyandu, as well as nutrition education. The primary objective of this program is to raise public awareness about the importance of following health protocols and to improve public health. Empowering the Kusuma Elderly Posyandu, creating health protocol media, and measuring the success of program implementation, monitoring, and evaluation are the three stages of the program implementation method. This program has been well-implemented, with mentoring and improved facilities to support the Kusuma Elderly Posyandu's activities. As a result of this activity, Kusuma's posyandu services for the elderly can now provide more comprehensive, orderly, and in-demand services to the local community, particularly the elderly.